Komunikasi Visual Partisipatif Untuk Meningkatkan Keterlibatan Masyarakat Dalam Edukasi Publik - Galang Prasetyo Nugroho (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study addresses the limited effectiveness of public education programs that are predominantly one-way and insufficiently involve communities in the design of visual messages. As a result, messages are often less contextual and harder to understand. This research aims to analyze the role of participatory visual communication in enhancing community engagement and understanding in public education programs. A descriptive qualitative approach using Participatory Action Research (PAR) was employed, involving 20 participants through observation, focus group discussions, visual design workshops, interviews, and documentation. Thematic analysis was conducted to identify patterns of participation and changes in understanding. The findings reveal five main forms of participation, with the highest engagement occurring during the media review stage. All indicators of message comprehension, discussion engagement, design contribution, and message application showed consistent descriptive increases ranging from 40% to 55%, based on proportional changes before and after the intervention, without inferential statistical testing. The novelty lies in integrating collaborative visual creativity with active community participation. Practically, this approach produces more relevant, inclusive, and applicable educational messages for community service programs.